2017
DOI: 10.1038/ncomms16072
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into the mycobacteria transcription initiation complex from analysis of X-ray crystal structures

Abstract: The mycobacteria RNA polymerase (RNAP) is a target for antimicrobials against tuberculosis, motivating structure/function studies. Here we report a 3.2 Å-resolution crystal structure of a Mycobacterium smegmatis (Msm) open promoter complex (RPo), along with structural analysis of the Msm RPo and a previously reported 2.76 Å-resolution crystal structure of an Msm transcription initiation complex with a promoter DNA fragment. We observe the interaction of the Msm RNAP α-subunit C-terminal domain (αCTD) with DNA,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 67 publications
11
51
0
Order By: Relevance
“…We found that ~25% of putative ECF σ promoters contained at least one UP-element subsite. UP-element subsites were preferentially located at the proximal, distal, and far-distal subsites ( Figure 4C), and the frequency of UP-elements varied by bacterial phyla, consistent with previous reports (Table 2; Hubin et al 2017).…”
Section: Predicted Ecf σ Promoters Are Similar To Experimentally Charsupporting
confidence: 91%
“…We found that ~25% of putative ECF σ promoters contained at least one UP-element subsite. UP-element subsites were preferentially located at the proximal, distal, and far-distal subsites ( Figure 4C), and the frequency of UP-elements varied by bacterial phyla, consistent with previous reports (Table 2; Hubin et al 2017).…”
Section: Predicted Ecf σ Promoters Are Similar To Experimentally Charsupporting
confidence: 91%
“…Holoenzyme structures complexed with RNA (PDB ID 5VT0 (62)) (A and C) and promoter DNA (PDB ID 5VI5 (84))(B and D) are centered on region 4.2 of σ 70 and shown without (A and B) or with (C and D) the nucleic acids visible. The cryoEM structure with 6S RNA is E. coli holoenzyme and the crystal structure with DNA in an open complex is Mycobacterium smegmatis holoenzyme and thus there are small variations in structure due to sequence changes, although region 4.2 of σ 70 is very highly conserved.…”
Section: Figurementioning
confidence: 99%
“…However, the structural details between 1.1 domains from different organisms vary widely. Currently, three types of known structures of this domain exist: (i) the highly similar structures, as solved for B. subtilis and E. coli, consisting of three helices (HI to HIII) packed in antiparallel manner (8,10); (ii) the structure from T. maritima, where HI packs perpendicularly to HII and HIII (9); and (iii) the possibly disordered and flexible structure from mycobacteria with only the A N-helix discernible (11)(12)(13)(14).…”
mentioning
confidence: 99%